The Implementation of the Authority of the Aceh Land Office in the Certification Process of Land Assets Owned by the Aceh Government - Elvira Wahyuni; Ilyas Ismail; Mahdi Syahbandir (International Journal of Law and Society, 2026)
Based on Law Number 11 of 2006 concerning the Government of Aceh, the Government of Aceh has been granted special authority to manage and regulate various governmental affairs, including land administration. This authority is specifically outlined in Article 16 paragraph (1) letter k, which empowers the Government of Aceh to handle land affairs that span across regencies and municipalities. This power is further reinforced by Presidential Regulation Number 23 of 2015, which transformed the Regional Office of the National Land Agency of Aceh into the Aceh Land Agency, and Qanun Aceh Number 13 of 2019 regarding the Establishment and Organizational Structure of Aceh Regional Apparatus, which laid the foundation for the establishment of the Aceh Land Office. This office is responsible for managing and certifying the Aceh Government’s land assets. This study aims to assess the implementation of the Aceh Land Office’s authority in certifying government land assets, the institutional synergy with the National Land Agency, and the challenges faced in ensuring legal certainty over these assets. The research employs an empirical juridical method with a sociological approach. Data were gathered from interviews with officials from the Aceh Land Office, the Aceh Financial Management Agency, and the National Land Agency, as well as secondary data from legal documents, books, and academic resources. The study found that while the certification process is legally supported, challenges such as incomplete ownership documents and limited resources hinder effective implementation. Measures, such as re-tracing and remapping land assets, are being taken to address these challenges.